The fast and the flexible: cognitive style drives individual variation in cognition in a small mammal. (March 2018) - Mazza, Valeria; Eccard, Jana A.; Zaccaroni, Marco; Jacob, Jens; Dammhahn, Melanie
Abstract : Patterns of individual differences in cognition have been studied empirically and systematically in the last decade, but causes and consequences of this variation are still largely unclear. A recent hypothesis suggests that one predictor of individual variation in cognition is personality, and specifically that personality types are linked to cognitive styles through a speed–accuracy trade-off. We tested specific predictions of this hypothesis, measuring individual differences in associative learning speed and flexibility, quantified via reversal learning, of 86 bank voles, Myodes glareolus, along with their activity and boldness. We found that bolder and more active individuals were fast, inflexible and persistent in the associative learning tasks, whereas shyer and less active individuals were slow and flexible. We also found evidence for a speed–accuracy trade-off: correct choices in the cognitive tasks required more time for all individuals compared to incorrect choices, but bolder, more active voles always made their decisions faster than reactive ones. The difference between the time required for a correct and an incorrect choice was most pronounced in initial learning for shyer and less active individuals, but for bolder, more active individuals it was most pronounced in the reversal learning task. We also found differences related to sex and age: females were faster than males to update information or correct incorrect choices and older animals took longer to initiate the test. Our results confirm the hypothesis that individual differences in behaviour are reflected in different 'cognitive styles', differentially trading off speed for flexibility and accuracy in cognitive tasks. Moreover, we provide the first evidence for the mechanisms of such a trade-off in a small mammal. Highlights: We tested personality, learning speed and flexibility in reversal in bank voles. Personality predicted learning speed, flexibility and persistence. Correct choices required more time than incorrect ones. Sex and age affected the cognitive strategy rather than the performance. Personality is linked to cognitive style, and should be included in cognitive research.